One-pot liquefaction of cellulose to ethyl levulinate via 1-sulfonic acid-3-methyl imidazolium trichlorozincate as Brønsted-Lewis catalyst - Krishnasamy, Kirrthana; Mohd Asraff, Asmadi; Nor Aishah Saidina, Amin; Muzakkir Mohammad, Mohammad Zainol; Zaki Yamani, Zakaria; Sureena, Abdullah (Elsevier Ltd, 2023)
The direct conversions of cellulose to ethyl levulinate (EL) via Brønsted acidic ionic liquid (BAIL), Lewis acidic ionic liquid (LAIL), and Brønsted-Lewis acidic ionic liquid (BLAIL) conducted in this study is a sustainable approach. Initially, BAIL 1-sulfonic acid-3-methyl imidazolium chloride [SMIM][Cl] was prepared by the mixing of 1-methylimidazole, dry dichloromethane, and chlorosulfonic acid. Then, Lewis acidic site was provided to the BAIL by the addition of zinc chloride (ZnCl2), to synthetize BLAIL 1-sulfonic acid-3-methyl imidazolium trichlorozincate, [SMIM][ZnCl3]. Meanwhile, LAIL 1-butyl-3-methyl imidazolium trichlorozincate [BMIM][ZnCl3] was prepared by the addition of ZnCl2 to a neutral 1-butyl-3-methyl imidazolium chloride [BMIM][Cl]. These three catalysts were then characterized and employed in the one-pot liquefaction process that was conducted in a stainless-steel batch reactor at 180 °C for 10 hr, by charging 0.6 g of cellulose, 40 mL of ethanol and 3 g of catalyst. A parameter study, mainly temperature (120-200) °C, time (2-10) hr, and cellulose loading (0.2-1.0) g, were then conducted to determine the selected parameters to obtain high EL yield. Among the employed ionic liquids (ILs), BLAIL [SMIM][ZnCl3] exhibited the highest catalytic activity, which was contributed mainly by its co-existence of Brønsted and Lewis acidic sites as detected in Fourier-Transform Infrared (FTIR) analysis, and its high acidic value. The maximum EL yield (20.27 wt%) was obtained under conditions of 180 °C, 6 hr, 0.6 of cellulose, and 3 g of [SMIM][ZnCl3]. The outcome of this study provides an insight on the potential of novel [SMIM][ZnCl3] in facilitating the direct cellulose ethanolysis to EL.